Legitimately distinct entrepreneurial stories in evolving market categories - Younger, Shannon; Preedom, Jonathan; Navis, Chad (Journal of Business Venturing, 2025)
We develop a theoretical framework explaining how the evolving uncertainty imperatives of the nascent, emerging, and mature stages of a market category influence the entrepreneurial stories that audiences judge as legitimately distinct. Our focus is on the sensemaking role of different story components in shaping these judgments, both independently and through their holistic interplay. We also relate these story components to the broader issues that audiences seek to resolve at each stage, which affects their potential resonance. This framework provides a contextualized understanding of legitimate distinctiveness and identifies unique tensions in each stage of an evolving market category, offering a valuable integration and advancement of existing scholarship.